PENGARUH PENGGUNAAN E-MODUL PENGAYAAN ISOLASI DAN KARAKTERISASI BAKTERI UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMA - Dyah Aniza Kismiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Nahdlatul Wathan Mataram, 2021)
This study aims to determine the effect of the use of enrichment e-modules in increasing the learning independence of high school students. This research is a quasi experimental study with nonequivalent pretest posttest control group design. The sample of the study is Jetis 1 High School students Bantul consisting of 2 classes. This sample was taken based on purposive sampling technique, class X MIPA 5 as a control class and class X MIPA 1 as an experimental class. The instruments used were questionnaires and observation sheets for students' learning independence. Data were analyzed through Independent Sample T-Test and Normalized Gain Score (N-Gain Score). The results showed that the E-module developed had a significant effect on student learning independence as evidenced by the significance value of 0,000 <Î± 0.05 and the category of moderate improvement from the calculation of N-Gain Score of 0.307. Keywords : E-modul, enhancement, bacteria, self regulation learning